2012
DOI: 10.2478/v10245-012-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability of carrot (Daucus carota L.) lines and heritability of yield and its quality components

Abstract: The purpose of this research was to investigate the combining ability of inbred lines in terms of traits important for the development of hybrid carrot cultivars with high yields and better root quality. The experimental plant material consisted of 15 inbred lines that were crossed in an incomplete diallel design to produce 34 hybrids. It was observed that the variation of general combining ability (GCA), specific combining ability (SCA) and reciprocal effects (RE) were significant for all of the tested charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Consequently, hybrid vigor was evident for root biomass, which had relatively high proportions of nonadditive genetic variation, significant estimates of an inbred penalty, and signals of pseudo-overdominance ( Figure 8 and Figures S47 and S53 in File S1 ). This result coincides with widespread evidence of heterosis in plants, whereby hybrids demonstrate increased developmental speed and greater biomass acquisition relative to their inbred parents ( Shull 1908 ; East 1936 ; Birchler et al 2003 ; Meyer et al 2004 ), and agrees with previous observations of hybrid vigor for root weight in carrot ( Simon et al 1982 ; Duan et al 1996 ; Simon and Strandberg 1998 ; Suh et al 1999 ; Jagosz 2011 , 2012 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, hybrid vigor was evident for root biomass, which had relatively high proportions of nonadditive genetic variation, significant estimates of an inbred penalty, and signals of pseudo-overdominance ( Figure 8 and Figures S47 and S53 in File S1 ). This result coincides with widespread evidence of heterosis in plants, whereby hybrids demonstrate increased developmental speed and greater biomass acquisition relative to their inbred parents ( Shull 1908 ; East 1936 ; Birchler et al 2003 ; Meyer et al 2004 ), and agrees with previous observations of hybrid vigor for root weight in carrot ( Simon et al 1982 ; Duan et al 1996 ; Simon and Strandberg 1998 ; Suh et al 1999 ; Jagosz 2011 , 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…Many carrot breeding programs employ the inbred-hybrid method, which is enabled by the widespread availability of cytoplasmic male sterility (CMS) in carrot germplasm ( Peterson and Simon 1986 ; Simon 2000 ). Accordingly, heterosis is considered a promising mechanism to increase yield in carrot ( Rubatzky et al 1999 ), and hybrid vigor has been documented for important traits such as carrot root yield ( Duan et al 1996 ; Suh et al 1999 ; Simon and Strandberg 1998 ; Jagosz 2011 , 2012 ; Simon et al 1982 ), carotenoid content ( Santos and Simon 2006 ), and resistance to Alternaria leaf blight ( Simon and Strandberg 1998 ). However, the development and adoption of heterotic groups in carrot remains limited, and has not been described in detail.…”
mentioning
confidence: 99%
“…The impact of environmental factors, e.g., planting density [ 2 ], water regime [ 3 ], soil forming [ 4 ], temperature [ 5 ], and nutrient availability [ 6 ] on carrot root growth have been described. It was also reported that heterosis resulted in increased carrot storage root biomass and improved its quality [ 7 ] and a strong linear relationship between shoot and root biomass was shown [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poucos trabalhos publicados na literatura apresentam estimativas da capacidade combinatória em cenoura. No entanto, alguns estudos mostraram a existência de heterose e a eficiência da utilização de análise dialélica, para a escolha de genitores e de combinações híbridas superiores (Duan et al, 1996;Simon & Strandberg, 1998;Guan et al, 2001;Jagosz, 2012;Carvalho et al, 2014).…”
Section: Introductionunclassified